Sex and hand differences in haptic processing: implications for mental rotation ability - Daniela E. Aguilar Ramirez; Claudia L. R. Gonzalez (Biology of Sex Differences)
Abstract It has been proposed that the sensorimotor system provides a foundation for the development of cognitive abilities and their hemispheric specialization. In this study, we investigated the potential relationship between haptic processing and mental rotation ability, both of which are typically lateralized to the right hemisphere. Previous research has also indicated that males tend to outperform females in both functions. The current study investigates how the sensorimotor-haptic system relates to mental rotation ability, specifically to examine the influence of hand performance (as a proxy for hemispheric specialization) and biological sex on this relationship. Seventy-five participants (n = 41 females) completed a haptic task, and the well-known mental rotation test (MRT) developed by Shepard and Metzler (Science 171:701–3, 1971). Results confirmed a positive correlation between performance on the haptic and MRT tasks. Further, males outperformed females in both tasks. However, when sex and hand performance were considered, males were better in the haptic task, but only when using their left-hand. Moreover, left-hand haptic performance was the sole predictor of MRT performance. These findings suggest that sex differences in haptic processing may contribute to the observed sex differences in mental rotation ability, supporting the view that sensorimotor processes shape cognitive function and its hemispheric lateralization.